Socio-demographic determinants of under-five mortality in rural Agra - Kumar, Krishan; Srivastava, Rajiv; Mishra, S. K. (International Journal Of Community Medicine And Public Health, 2017)
Background: One of the most important indicator or index of socio-economic development of a country or region is infant mortality rate. The present study was undertaken to assess the quantum of childhood mortality and to find out the social factors associated with these deaths by verbal autopsies. Methods: This one year cross-sectional study was undertaken in a purposively selected community Development Block Sainyan, district Agra among children aged between 0-5 years using multistage random sampling technique. Suitable statistical methods were applied. Results: Out of total 8355 families surveyed, a total of 185 deaths were reported among children. Number of deaths was higher among those belonging to nuclear family and lower socioeconomic status. The neonatal mortality rate was estimated to be 33.55/1000 live births. The post neonatal mortality rate was found to be 40.78/1000 live births and infant mortality rate was 74.33/1000 live births. Mortality rate in 1-5 year age group children was 10.6/1000 same age group children, while 0-5 yrs. mortality was estimated to be 22.39/1000 children of same age group. Out of 185 children who died, 52.7% were unimmunized and another 35.67% were partially immunized. Conclusions: Female education and socioeconomic well-being should be strengthened.